Eficiência energética em sistemas de iluminação artificial: o caso do DAU-UFC-Ce - Castro filho, Joel de Lima (2022)
Artificial lighting is an indispensable element in today's human life. However, its use in any space requires the adoption of not only quantitative but also qualitative criteria. As for the amount of lighting, this is a criterion that depends on the space being worked on. As for quality, it is important to keep in mind that this is not obtained only by worrying about the types of light sources (lamps) to be used in the environment, as quality in artificial lighting systems also means concern with materials, textures and colors used in the surroundings as well as the correct positioning of light sources. The lighting industry has been growing and investing, incessantly, in energy savings and equipment efficiency through new revolutionary technologies. In recent years, many artificial lighting products have been developed for this purpose: economy and efficiency. The results are getting better, that is, better quality lighting and significant energy reduction. The research aimed to verify the conditions of artificial lighting and identify the possibility of reducing electrical energy consumption through the case study in the DAU - UFC, where a retrofit proposal was made based on the survey of the current lighting situation. The survey found that the current system situation for more energy efficient technologies, reduces lighting consumption by at least 43.5%. The value of this percentage of consumption reduction can still be increased by the implementation of measures that supervise the correct use of the lighting system and equipment, the control in the acquisition of new technologies and the adoption of educational programs destined to the development of anti-waste policies aiming to guide users for the best and most correct use of deployed resources.